(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article reveals important opportunities that allow the implementation of the main ideas of pedagogical coaching in teaching students a foreign language in the educational space of a modern university. These opportunities are considered in accordance with the main trends noted in the development of the higher education system of our country in recent years. At the same time, both positive and negative trends in its development are taken into account. Various examples of learning tasks used within this methodology are considered.